Student Learning Needs in Basic Machining Practices in the Department of Mechanical Engineering Education - Andrian Riyadi; Andhita Mustikaningtyas; Arya Yusuf; Zevanya Valerina Zahra (Universitas Sultan Ageng Tirtayasa, 2025)
This research was conducted in order to answer problems in terms of learning basic machining practices where increasingly advanced technology requires the use of equipment and teaching materials that are increasingly advanced as well to form student competencies needed by the world of work. This study aims to determine the needs of students in learning basic machining practices at the Department of Mechanical Engineering Education FT UNY. The research method used is descriptive quantitative using a free description questionnaire in the form of Google Form as a data collection instrument. The population of this study were the 1st year students of the Mechanical Engineering Education study program, while the sample was the 33 students of 1st year students at Mechanical Engineering Education study program who were taking basic machining practice courses. The results of the research showed that 100% of students stated that it needs improvement on workshop facilities and infrastructure, 33.3% of students stated the needs to increase the skills and abilities of lecturers, 36.4% of students stated the needs of the skills and abilities of technicians, and 42.4% of students stated the needs of improvement on teaching materials. In conclusion, students need improvement in various aspects of learning, even though some students are satisfied with their current learning.